A retrospective analysis of acute kidney injury in children with post-COVID-19 multisystem inflammatory syndrome: insights into promising outcomes - Hanan El-Halaby; Riham Eid; Ahmed Elagamy; Ahmed El-Hussiny; Fatma Moustafa; Ayman Hammad; Mayada Zeid (BMC, 2024)
Abstract Background Acute kidney injury (AKI) in patients with multisystem inflammatory syndrome (MIS), COVID-19 related infection has been increasingly recognized with a paucity of data on AKI incidence, related mortality, and the requirement of renal replacement therapy in children with MIS (MIS-C). Methods This is a retrospective study evaluating the prevalence, severity, management and outcomes of AKI in a cohort of Egyptian children with MIS-children (MIS-C) post-COVID infection. Patients were included if they met the criteria for MIS-C based on CDC guidelines. All patients were evaluated for AKI diagnosis and staging according to the Kidney Disease Improving Global Outcomes (KDIGO) criteria. Results Between March 2021 and June 2023, a total of 655 confirmed COVID-19 cases were admitted and then followed up in our hospital, of whom 138 (21%) were diagnosed with MIS-C. Fifty-one patients developed AKI associated with MIS-C post-COVID infection, 42 of whom were included in the analysis. Thirty-one patients had AKI in a formerly healthy kidney, of whom 51% (16 patients) were classified as KDIGO stage 3, 5 patients needed hemodialysis and 13 needed mechanical ventilation. Higher WBCs count, and serum ferritin on admission were associated with more severe AKI (KDIGO stage 3) (p = 0.04), while multivariate analysis showed high serum ferritin to be independent predictor of more severe AKI (p = 0.02). Two patients (2/31) died during hospital admission, while no residual renal impairment was reported at the time of discharge of patients with previously normal kidney functions. Conclusion More than one-third of patients with MIS-C develop AKI. Avoidance of nephrotoxic drugs, early recognition, and prompt management of AKI, including well-timed commencement of dialysis in MIS-C cases, is associated with favorable outcomes.